ANALISA HARGA POKOK PRODUKSI PEMBUATAN BARANG TIANG PJU OCTAGONAL PADA CV. ENERGREEN INDONESIA - Abdul Aziz; Soesilawati Soema Atmadja; Khakim, M. Azizul (Ekomania, 2023)
Determination of the cost of goods manufactured is very important, because it can increase the competition that occurs between company in producing quality products at competitive prices. This study aims to analyze the cost of goods manufactured of octagonal PJU poles and analyze the comparison of the company's cost of goods manufactured with the full costing method of CV. Energreen Indonesia, Sidoarjo from February to May 2021. This research was conducted with a qualitative method, namely a survey and conducted on a sample selected to represent the entire population with an individual unit of analysis. company owners and observations, as well as secondary data sourced from literature studies and other literature that support the writing of this research. The results of the study found that the calculation of the cost of goods manufactured using company method for the single parabolic pole PJU octagonal H 7000 was Rp. 175.505.000, and from the double parabolic pole PJU octagonal H 7000 was Rp. 188,715,000. And in calculating the cost of goods manufactured according to the full costing method is better than the company's method in analyzing production costs, this is because the calculation of the cost of goods manufactured using the full costing method does not include general and administrative expense. become overhead costs, because these costs are a component of costs on the company's income statement